Analysis Of Food Order Scheduling Dine-In In Sengkaling Culinary Malang - Verawati, Shintia; Supriyati, Triningsih Sri; Fuadiputra, Iqbal Ramadhani (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
Sengkaling Culinary is a service company engaged in the culinary field of food and beverages. This study aims to find out and analyze how to schedule production at Sengkaling Kuliner Restaurant to minimize waiting time for orders. The analytical tool used is the priority rule method with the sorting method consisting of FCFS, SPT, LPT, EDD, and Gantt charts. The results showed that the SPT and EDD methods were the best methods that could be applied to restaurants with an average completion time of 9.02 minutes, 0.53% utilization, an average of 1.86 jobs, and a delay of 2.89 minutes. The advice given to the company is to make improvements to the Sengkaling Kuliner production process by using job sequencing based on the SPT and EDD methods.